26 Fairmount Avenue - DePaola, Tomie, 1934-2020- (DePaola, Tomie, 1934-2020- 26 Fairmount Avenue book., 1999)
Children's author-illustrator Tomie De Paola describes his experiences at home and in school when he was a boy.